2014
DOI: 10.12703/p6-13
|View full text |Cite
|
Sign up to set email alerts
|

The M1 and M2 paradigm of macrophage activation: time for reassessment

Abstract: Macrophages are endowed with a variety of receptors for lineage-determining growth factors, T helper (Th) cell cytokines, and B cell, host, and microbial products. In tissues, macrophages mature and are activated in a dynamic response to combinations of these stimuli to acquire specialized functional phenotypes. As for the lymphocyte system, a dichotomy has been proposed for macrophage activation: classic vs. alternative, also M1 and M2, respectively. In view of recent research about macrophage functions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

80
3,521
4
49

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,785 publications
(3,814 citation statements)
references
References 107 publications
80
3,521
4
49
Order By: Relevance
“…Moreover, chitinase (Ym1) expression found only in M2a cells [9] increased to a high level under M2a polarizing conditions. These results were in accordance with previous data [37]. The presence of MSCs did not cause a change in the level of IL-10 or Ym1, however significantly downregulated TNF in M1 and M2b cells and upregulated in M2a Ms although to a very low level.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, chitinase (Ym1) expression found only in M2a cells [9] increased to a high level under M2a polarizing conditions. These results were in accordance with previous data [37]. The presence of MSCs did not cause a change in the level of IL-10 or Ym1, however significantly downregulated TNF in M1 and M2b cells and upregulated in M2a Ms although to a very low level.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple subpopulations of M2 cells have been determined, each with a different phenotype and stimulus. M2a (alternative activation) subpopulations respond to IL‐4 and IL‐13 and are associated with parasitic defense and Th2 cell response; M2b (type II alternative activation) cells are stimulated with IL‐1 and ligation of CD16, CD32, and CD64 and are associated with immunoregulation; M2c (acquired deactivation) subpopulations are stimulated via IL‐10 and glucocorticoids, have increased expression of TGFβ and CD163, and are important in tissue remodeling and immunoregulation (Martinez & Gordon, 2014; Walker & Lue, 2015). LXA 4 has been shown to induce phagocytosis and debris clearance in macrophages, an important characteristic of M2 cells (Godson et al., 2000; Vasconcelos et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Much of what we know of the phenotypes of microglia and macrophages are from in vitro experiments, which do not accurately convey the complexity of an in vivo system, especially one with injury. Many studies fail to mimic the in vitro reports of macrophage subpopulations in a disease model in vivo (Davies, Jenkins, Allen, & Taylor, 2013; Martinez & Gordon, 2014). It is possible that the population of CD163 + cells in the BML‐111 rat brains are not secreting IL‐10 but instead are more dynamic and secreting other anti‐inflammatory or neuroprotective factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By transcellular pathways AA can be converted to proresolving lipoxins (LXs), generated via 15-LO-1 and 5-LO or by 5-LO and 12-LO (7). Recently it was reported that LXA 4 and 15-epi-LXA 4 could also be formed within one cell type (murine RAW264.7 and bone marrow-derived Mfs) (8). Depending on the expression and activation of eicosanoid-forming enzymes and their proximity to cPLA 2 , cells may preferentially shunt AA toward one of these pathways (6).…”
mentioning
confidence: 99%